Effect of scopolamine on action potential of myocardial cell of guinea pig - LI Zhen-yuan (Acta Pharmacologica Sinica, 2016)
Action potential of myocardial cell of isolated ventricular septum was recorded by intracellular capillary glass electrode. The duration of action potential (APD) was prolonged from 91±31 ms and 142±39 ms to 115±35 ms and 179±50 ms for APD50 and APD100, respectively by scopolamine 50 μg/ml (p